Potencialização da síndrome dolorosa induzida por paclitaxel pela inibição da enzima conversora de angiotensina e o envolvimento das cininas - Brusco, Indiara (2016)
Paclitaxel is a chemotherapeutic agent widely used in the treatment of solid tumors. However, it causes adverse effects that limit their use, such as acute pain syndrome and peripheral sensory neuropathy. These sensory changes lead to dose reduction or discontinuation of therapy compromising the quality of life of patients. Among the mechanisms involved in neuropathic pain is activation of kinin receptors. The activation these receptors trigger nociceptive and inflammatory responses. Moreover, the signaling these receptors can be enhanced by angiotensin I-converting enzyme (ACE) inhibitors which inhibit the degradation of kinins. Although studies have shown the involvement of kinins on paclitaxel-induced neuropathy, there are no studies on its role in acute painful syndrome caused by this chemotherapy. Furthermore, it is not known the relationship between the kinin receptors and the acute or chronic hypersensitivity caused by paclitaxel during ACE inhibition. Thus, we evaluated the role of kinin receptors and the effect of the ACE inhibition on acute and neuropathic pain syndrome associated with paclitaxel. For induction of acute and chronic painful syndrome mice received single or repeated administration of paclitaxel, respectively. The role of kinin receptors was investigated using antagonists of these receptors. In order to investigate the effect of the ACE inhibition on paclitaxel-induced painful syndrome the animals received a low dose of paclitaxel plus enalapril (ACE inhibitor). Mechanical hyperalgesia was assessed using the von Frey filaments and the spontaneous nociception by time of paw licking induced by B1 (Bradykinin) and B2 (des-Arg9-bradykinin) receptors agonists. It was also evaluated the expression of the B1 and B2 receptors in the sciatic nerve, the bradykinin-related peptides levels and ACE activity in plant tissue, serum and sciatic nerves of animals. We observed that paclitaxel caused mechanical hyperalgesia and spontaneous nociceptive behaviour that was reduced by antagonists of kinin receptors B1 (DALBk and SSR240612) and B2 (Hoe140 and FR173657). Moreover, the ACE inhibitor enhanced the mechanical hyperalgesia induced by a low dose of paclitaxel. Likewise, paclitaxel injection inhibited ACE activity in the sciatic nerve and in the plantar tissue, increased expression of B1 and B2 receptors in the sciatic nerve and increased bradykinin-related peptides levels in the plantar tissue. Together, our data support the involvement of kinin receptors in the acute or chronic pain hypersensitivity paclitaxel-induced and suggest kinin receptor antagonists to treat this painful syndrome. Because hypertension is the most frequent co-morbidity affecting cancer patients, treatment of hypertension with ACE inhibitors in patients undergoing paclitaxel chemotherapy should be reviewed, since ACE inhibitors could enhance the paclitaxel-induced pain syndrome.